Factors impacting user acceptance of e-wallets in Bangladesh's transition towards a cashless society - Tanha, Moutusi; Islam , Nurul; Priya, Farhana Akter; Emran, Mohammad Zonaed; Mahmud , Tanvir; Mortuza, Md. (Annals of Management and Organization Research, 2024)
Purpose: This study investigates the impact of the digital revolution on everyday life, focusing mainly on the emergence of e-wallets as substitutes for traditional physical wallets, and the adoption of various banking technologies in Bangladesh. Research Methodology: This study examines the utilization of several banking technologies in Bangladesh, including bKash Limited's mobile banking services, which were introduced in July 2011, and offer secure and convenient financial services to individuals with or without bank accounts. Additionally, this study explores the National Payment Switch developed by Bangladesh Bank in 2012, which aims to standardize electronic payments among commercial banks, facilitating cash withdrawals using plastic cards at ATMs and point-of-sale (POS) locations. Results: The findings indicate that bKash Limited's mobile wallet facilitates secure transactions through its highly encrypted Visa technology platform, enabling customers to deposit for various services such as wages, loans, and domestic remittances. However, the availability of bKash is limited to specific networks and areas, with restrictions on the use of bank accounts. Moreover, implementing the National Payment Switch is expected to reduce transaction costs, enhance financial inclusivity, and streamline online transactions by eliminating individual payment networks. Limitations: One limitation of the study is the limited availability of bKash in specific regions and networks, and the restrictions imposed on bank account usage within the system. Contribution: This study contributes to the understanding of the evolving landscape of digital banking technologies in Bangladesh by offering insights into the adoption and impact of e-wallets and other banking solutions. The findings may inform policymakers, financial institutions, and researchers about strategies to enhance financial inclusivity, reduce transaction costs, and promote digitalization in the banking sector.